795 A POSITIVE 4AT DELIRIUM ASSESSMENT TOOL SCORE ON HOSPITAL ADMISSION IS LINKED TO MORTALITY, LENGTH OF STAY AND 'HOME TIME': A STUDY OF 82, 770 HOSPITAL ADMISSIONS IN EDINBURGH AND SALFORD. (8th March 2022) - Vardy, E R L C; Anand, A; Cheng, M; Ibitoye, T; MacLullich, A M J
Abstract: Introduction: Delirium is linked with poor outcomes but studies using large-scale routine data are scarce. The 4AT (www.the4AT.com ) is a brief ( 2 minutes), well-validated tool for detection of delirium and cognitive impairment. We performed a two-centre study (Edinburgh and Salford) of Electronic Health Record (EHR) 4AT scores and outcomes in 82, 770 non-elective hospital admissions in patients aged ≥65. We determined relationships between 4AT scores 0 (no impairment), 1–3 (cognitive impairment but no delirium) and ≥ 4 (delirium), in relation to 30-day inpatient mortality, length of stay, and time at home ('home time') in the year following index admission. Methods: We analysed EHR 4AT scores recorded within 24 hours of admission, and outcomes data were also derived from the EHR. The study period was between April 2016 (Edinburgh)/September 2017 (Salford) and April 2020 (both centres). Results: 4AT scores suggestive of delirium (≥4) were present in 25% in Salford, and 18% in Edinburgh. After adjustment for age and sex, 30-day inpatient mortality with 4AT ≥4 was 5.5-fold greater than the 4AT 0 group in Edinburgh (aOR 5.53, 95% confidence interval [CI] 4.99–6.13) and 3.4-fold greater in Salford (aOR 3.39, 95% CI 2.98–3.87). Length of stay was more than double in patients with any abnormal 4AT score compared to a 4AT score of 0. The median 'home time' at 1 year was reduced by 112 days (Edinburgh) and 61 days (Salford) in the 4AT ≥4 compared to 4AT 0 days. Conclusions: This large study using routine clinical data confirms the relationships between delirium and poor outcomes previously reported in smaller research studies. Further, the results demonstrate the feasibility and value of using a brief clinical tool to identify delirium as a strong marker of adverse outcomes, and will be helpful in guiding policy development around patient safety including better treatment of delirium.